Comparative Semantics of Programming Languages - Mayoh, Brian H. (DAIMI Report Series, 1984)
The flood of new programming and specification languages shows no sign of abating, but very few of these languages have a formal definition. The advantages of knowing precisely what is specified in a specification and exactly how a program can behave are obvious, but none of the existing formal definition methods are completely satisfactory. Theoreticians have not been idle, but they have concentrated on problems that are not immediately relevant to language designers (algebraic and categoric structuring of definitions, refined notions of concurrency and the like). In the belief that the answer to some of the language designers’ problems is ’’use different formalisms to define fragments of the languages precisely’’, we advocate the study of comparative semantics. This paper is a contribution to this study, prompted by the fact that the parallel aspects of ADA seem to require a quite different kind of formal semantics from that used for sequential ADA in ’’Formal Definition of ADA’’, CII Honeywell Bull, 1981, Paris.